If I ruled the world. - Gough, Julian (Prospect, 2010)
The article discusses the author's view on the reduction of government spending on education by 100 billion pounds in Great Britain. The author recalls the introduction of compulsory schooling by the Perussians in 1763 where children were forced to learn by threat of violence compared to modern education with the help of technology. In addition, children who speak English-language were not only taught by good teachers but because they watch English-language television and listen popular music.